Microbiological study of empyema thoracis among children in a tertiary care hospital - Sagarika Dhal; Jyoti Ranjan Champatiray; Dibya Prasana Mohanty; Lalmohan Mishra; Manoj Kumar Dehury; Dharma Niranjan Mishra (Asian Journal of Medical Sciences, 2023)
Background: Empyema thoracis is a condition resulting in the accumulation of purulent fluid in the pleural cavity. It is a common source of illness among young children and is the most common sequela of bacterial pneumonia. Aims and Objectives: This study was to determine the clinico-microbiological profile, causative agents, and antimicrobial susceptibility patterns of the isolates of the study population. Materials and Methods: Prospective observational study was done in the Department of Microbiology, S. C. B. M. C. H., Cuttack. The study group comprised a total of 105 cases of empyema thoracis between the age group of 0–14 years, diagnosed by aspiration of pus from the pleural space. Complete histories of cases in detail were noted. Results: A total of 41% of patients were in the age group of 5–9 years with M: F ratio of 1.1:1. Maximum cases 36 (34.3%) were seen in the spring season. Fever, cough, and breathlessness were the most common complaints. Bronchopneumonia 56 (53.3%), impetigo, and skin lesions 29 (27.6%) were the major predisposing factors. Right-side empyema 71 (67.6%) was more common than the left side 34 (32.4%). Culture revealed Staphylococcus aureus as the most common etiologic agent 26 (36.1%), of which 30.8% were methicillin-resistant S. aureus, followed by Mycobacterium tuberculosis complex 13 (18.1%). Finally, 103 (98.2%) empyema cases were recovered by antibiotics and tube thoracostomy. Conclusion: Empyema thoracis is more prevalent in the lower socioeconomic population which can be prevented by an early diagnosis of pneumonia. Effective methods to treat empyema thoracis in children include the administration of proper antibiotics and tube thoracostomy in resource-poor settings.